ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI EKSPLOITASI PEKERJA ANAK DI INDONESIA MENGGUNAKAN REGRESI LOGISTIK BINER - Wardana, Lissa Octavia; Sari, Liza Kurnia (Indonesian Journal of Statistics and Applications, 2020)
Every child has human rights to grow and develop as a whole, both physically and mentally. The government prohibits employers from employing children to protect children's rights. In reality, children begin to participate in economic activities as workers. The issue of child labor is very close to exploitation. This research aims to find general facts about exploitation on child laborers and to identify variables that influence exploitation on child laborers in Indonesia in 2018. Data of National Social and Economic Survey (Susenas) in 2018 were analyed through binary logistic regression. The result shows that most of child laborers in 2018 are exploited. Provinces with the highest percentage of child laborers exploitation are DKI Jakarta, Banten, and Central Java. Area of residence, child labor sector, gender of child, and education of household head in the category of junior high school, elementary school, or not graduate from school significantly influence the exploitation of child labor. Child laborers who live in urban areas, male, work in the formal sector, and has a household head who graduate from junior high school or elementary school or doesn’t graduate at all are more likely experience exploitation.